The Effect of Work Discipline, Motivation, and Work Stress on Employee Job Satisfaction - Gultom, Parapat; Sipayung, Aquinaldo Boyfame R.; Hasibuan, Gamal Ali Akbar (Institut Bisnis dan Informatika Kesatuan, 2024)
This research was conducted with the aim of paying attention to how human resource control, planning processes, organizing, staff placement, direction and control are needed. This research focuses on the influence variables of discipline, work motivation, work stress which are then used to assess employee job satisfaction. The research method carried out used quantitative methods with a population of all employees at PTPN III. The type of data available is primary data. Sample data with 26 questionnaire questions was collected on Google Forms media. Data processing uses descriptive statistical test techniques, multiple linear regression tests, coefficient of determination tests, f tests, t tests, and Moderate Regression Analysis (MRA) tests. Data processing shows work discipline has a significant effect on job satisfaction, while work motivation and work stress do not have a significant effect on job satisfaction. The work environment is able to moderate the relationship between the influence of work discipline on job satisfaction. The work environment is unable to moderate the relationship between the influence of work motivation on job satisfaction. The work environment is able to moderate the relationship between the influence of work stress on job satisfaction.